COMMUNICATION IN THE TEACHER’S ACTIVITY AND ITS PSYCHOLOGICAL SYSTEM - Rasulova, Zukhra (Журнал иностранных языков и лингвистики, 2020)
THIS ARTICLE IS ABOUT COMMUNICATION IN THE TEACHER’S ACTIVITY AND ITS PSYCHOLOGICAL SYSTEM